Tools for teaching biochemistry and molecular biology: A parallel session at the IUBMB/PSBMB 2019 "Harnessing Interdisciplinary Education in Biochemistry and Molecular Biology" conference. Issue 6 (31st October 2020) - Chou, Chia‐Cheng; Provost, Joseph J.; Waye, Mary Miu Yee; Yu, Gracia Fe B.; Macaulay, Janet O.
Abstract: Approaches to learning and teaching have been undergoing massive changes. Technology has enabled many innovations while other methods have embedded authentic research approaches or looked to other disciplines. The tools in education session of the conference looked at tools being used to teach biochemistry and molecular biology ranging from online platforms, authentic research experiences to the use of music.